2014
DOI: 10.1093/cvr/cvu225
|View full text |Cite
|
Sign up to set email alerts
|

ESC Working Group Cellular Biology of the Heart: Position Paper: improving the preclinical assessment of novel cardioprotective therapies

Abstract: Ischaemic heart disease (IHD) remains the leading cause of death and disability worldwide. As a result, novel therapies are still needed to protect the heart from the detrimental effects of acute ischaemia–reperfusion injury, in order to improve clinical outcomes in IHD patients. In this regard, although a large number of novel cardioprotective therapies discovered in the research laboratory have been investigated in the clinical setting, only a few of these have been demonstrated to improve clinical outcomes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
138
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(139 citation statements)
references
References 135 publications
(167 reference statements)
0
138
0
Order By: Relevance
“…Hundreds of interventions have been performed in experimental studies with a view to limit ischemic injury but to date, interventions intended to improve patient outcomes have been disappointing. This may be due to various factors including, among others, poorly designed pre-clinical studies prior to embarking on clinical trials, inadequate pharmacological studies, complexities of the human in vivo model, and inadequate design of clinical studies to test cell protection therapies [101][102][103][104]. A short summary of emerging treatments is provided here; however, we recommend the reader consult the wealth of scientific publications on this subject already available in the literature.…”
Section: Myocardial Protection Strategiesmentioning
confidence: 99%
“…Hundreds of interventions have been performed in experimental studies with a view to limit ischemic injury but to date, interventions intended to improve patient outcomes have been disappointing. This may be due to various factors including, among others, poorly designed pre-clinical studies prior to embarking on clinical trials, inadequate pharmacological studies, complexities of the human in vivo model, and inadequate design of clinical studies to test cell protection therapies [101][102][103][104]. A short summary of emerging treatments is provided here; however, we recommend the reader consult the wealth of scientific publications on this subject already available in the literature.…”
Section: Myocardial Protection Strategiesmentioning
confidence: 99%
“…Over the past 3 decades, a number of pharmacological cardioprotection strategies were discovered in experimental studies (9). Researches involved conditioning mechanisms have revealed multiple receptors, pathways and end effectors, all of which can be pharmacologically stimulated, such as agents acting on cardiomyocyte receptors (adenosine, bradykinin, opioids, glucagon-like peptide 1, atrial natriuretic peptide, erythropoeitin, insulin), agents acting on intracellular signal transduction pathways (phosphodiesterase-5 inhibitors, glyceryl trinitrate or nitroglycerin, atorvastatin, delcasertib, nicorandil) and agents acting on the mitochondria (cyclosporine-A) (10)(11)(12)(13).…”
mentioning
confidence: 99%
“…However, none has been translated into clinical practice with the exception of early reperfusion (14)(15)(16). The reasons for the failure to translate pharmacologic conditioning strategies of cardioprotective effects from the bench to bedside have been extensively discussed in the literatures (3,(8)(9)(10)(11)(14)(15)(16)(17)(18)(19). Some experts concluded that the causes of failure can be attributed to inadequacy animal IRI models used in the preclinical cardioprotection studies.…”
mentioning
confidence: 99%
See 2 more Smart Citations